Denial of genocides in the twenty-first century - Der Matossian, Bedross, 1978- (Lincoln : University of Nebraska Press, 2023)
"Denial of Genocides in the Twenty-First Century discusses genocide denial in the twenty-first century by concentrating on communication, social networks, and public spheres of daily life"--
"Throughout the twenty-first century, genocide denial has evolved and adapted with new strategies to augment and complement established modes of denial. In addition to outright negation, denial of genocide encompasses a range of techniques, including disputes over numbers, contestation of legal definitions, blaming the victim, and various modes of intimidation, such as threats of legal action. Arguably the most effective strategy, however, has been denial through the purposeful creation of misinformation. Denial of Genocides in the Twenty-First Century brings together leading scholars from across disciplines to add to the body of genocide scholarship that is challenged by denialist literature. By concentrating on factors such as the role of communications and news media, global and national social networks, the weaponization of information by authoritarian regimes and political parties, court cases in the United States and Europe, freedom of speech, and postmodernist thought, this volume discusses how genocide denial is becoming a fact of daily life in the twenty-first century"--
Introduction: Genocide denial in the 21st Century / Bedross Der Matossian -- 1. Denial of genocide of Indigenous people in the United States / Robert K. Hitchcock -- 2. Armenian genocide and its denial: a comprehensive tool of supremacism? / Talin Suciyan -- 3. "Weaponizing the First Amendment": denial of the Armenian genocide and the U.S. courts / Marc A. Mamogonian -- 4. Coalition politics and parliamentary failure: the Armenian genocide bill in Israel's political arena / Eldad Ben Aharon -- 5. Denying the Shoah: distorting history in the 21st Century / Gerald J. Steinacher -- 6. Aversions to acknowledging the Khmer Rouge genocides in Cambodia, 1990-2021 / Ben Kiernan -- 7. Denial of the Guatemalan genocide, 1981-2020 / Samuel Totten -- 8. Regional political implications of Bosnian genocide denial / Jelena Subotić -- 9. Mainstreaming the denial of the genocide against the Tutsi / Roland Moerland -- 10. A multifront war of narratives: the Assad Regime's emerging denialism / Uğur Ümit Üngör and Annsar Shahhoud -- Epilogue / Israel W. Charny -- Notes -- Index.
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Genocide -- History -- 21st century; Génocide -- Histoire -- 21e siècle.; POLITICAL SCIENCE / Genocide & War Crimes; SOCIAL SCIENCE / Media Studies; Genocide; 2000-2099; History